Analytical evaluation of nonlinear distortion effects on multicarrier signals - Dinis, Rui (2017)
Due to their ability to support reliable high quality of service as well as spectral and power efficiency, multicarrier modulation systems have found increasing use in modern communications services. However, one of the main drawbacks of these systems is their vulnerability to nonlinear distortion effects. Analytical Evaluation of Nonlinear Distortion Effects on Multicarrier Signals details a unified approach to well-known analytical results on memoryless nonlinearities that takes advantage of the Gaussian behavior of multicarrier signals.